Assessment of Drug-Resistant Tuberculosis within the Decentralized Health System in Kenya and the Associated Treatment Outcomes - David Mutabari; Dr. Idah Orowe; Dr. Anthony Karanja; Dr. Hillary Kipruto (Annals of Medicine and Medical Sciences, 2024)
Background: In Kenya, health is a devolved function that county governments run. Tuberculosis is managed at the county level in coordination with the National Leprosy Tuberculosis and Lung Disease Program (NLTP), which has a mission of End TB Strategy to achieve a 95% decline in deaths due to tuberculosis compared with the 2015 baseline and reach an equivalent 90% reduction in tuberculosis incidence rate. Methods: This was a retrospective study that included patients who tested positive for drug-resistant tuberculosis from 2014 to 2019. Data was sourced from NLTP Electronic Medical Records. After abstraction, the data was entered into Excel and analyzed through STATA software version 13. Results: Of the 2674 enrolled patients in total, there were more males affected with DRTB at 64 % compared to the female patients. The public facilities carried the immense burden of diagnosis and treatment of the patient, having a cumulative number of 83 %, while the prison sector had the lowest number. For the resistance pattern, the new, relapse, and failure of first-line drugs accounted for most drug-resistant cases at 80 %, with only 65 % of the total cases having been done a gene-expert test at the point of screening. Conclusion: Kenya's devolved health system needs more coordinated support from the national government to the county health units for TB surveillance. Regional centralized laboratories for diagnosis and monitoring of TB would reduce the time it takes for samples to come to Nairobi for testing, which takes time before patents are initiated on treatment.